Review of the epidemiology and burden of ulcerative colitis in Latin America. (July 2020) - Kotze, Paulo Gustavo; Steinwurz, Flavio; Francisconi, Carlos; Zaltman, Cyrla; Pinheiro, Marcia; Salese, Leonardo; Ponce de Leon, Dario
The incidence and prevalence of ulcerative colitis (UC) has been reported to be rising in newly industrialised regions, such as Latin America. Here, we review data from published studies reporting demographics and clinical aspects of UC in Latin America to further understand epidemiology and disease burden. The incidence and prevalence of UC in Latin America varied between regions and studies, ranging between 0.04 to 8.00/100, 000 and 0.23 to 76.1/100, 000, respectively, and generally increased over the period from 1986 to 2015. The majority of patients with UC were female (53.6–72.6%) and urban residents (77.8–97.4%). Extraintestinal manifestations were reported in approximately 26–89.4% of patients. Use of biologic therapies was generally low (0.8–16.2%), with the exception of Mato Grosso do Sul, Brazil, with a greater proportion of patients tending to receive 5-aminosalicylates, immunosuppressants or corticosteroids; colectomy rates varied between studies (1.5–22%). A high proportion of patients had moderate to severe UC (45.9–73.0%) and, in 11 of 19 studies, the greatest proportion of patients had extensive disease (pancolitis). Colorectal cancer (0–1.7%) and mortality rates (0–7.6%) were low. This evaluation of published studies may influence therapeutic approaches and the development of strategies to improve healthcare access and patient outcomes, although further high-quality studies are required in patients with UC in Latin America.